Smart load scheduling strategy utilising optimal charging of electric vehicles in power grids based on an optimisation algorithm - Lu, Maxim; Abedinia, Oveis; Bagheri, Mehdi; Ghadimi, Noradin; Shafie‐khah, Miadreza; Catalão, João P.S. (IET, 2020)
One of the main goals of any power grid is sustainability. The given study proposes a new method, which aims to reduce users’ anxiety especially at slow charging stations and improve the smart charging model to increase the benefits for the electric vehicles’ owners, which in turn will increase the grid stability. The issue under consideration is modelled as an optimisation problem to minimise the cost of charging. This approach levels the load effectively throughout the day by providing power to charge EVs’ batteries during the off‐peak hours and drawing it from the EVs’ batteries during peak‐demand hours of the day. In order to minimise the costs associated with EVs’ charging in the given optimisation problem, an improved version of an intelligent algorithm is developed. In order to evaluate the effectiveness of the proposed technique, it is implemented on several standard models with various loads, as well as compared with other optimisation methods. The superiority and efficiency of the proposed method are demonstrated, by analysing the obtained results and comparing them with the ones produced by the competitor techniques.
Keywords: fi=Sähkötekniikka|en=Electrical Engineering|